ARTYKUŁ PRZEGLĄDOWY/REVIEW PAPERPrinciples of the reasonable serodiagnostic of the “marker” autoantibody in Ctd-s - Ząbek, Jakub (Reumatologia/Rheumatology, 2005)
In most of the autoimmune diseases, a humoral and cellular immune response is characteristically seen, with autoantibodies and cells directed to distinct nuclear antigens (ANA). This phenomenon can be shown in systemic diseases like sclerosis, systemic lupus erythematosus, Sjögren’s syndrome, mixed connective tissue disease, polymyositis and rheumatoid arthritis. The presence of autoantibodies is important items to be considered in establishing a diagnosis and because of that autoantibodies are included in the diagnostic criteria of many autoimmune diseases. They are useful prognostic markers in some situations and facilitate clinical and treatment follow-up. It seems to us the indirect immunofluorescence method (IIF) was a most powerful, sensitive and comprehensive test for screening of autoantibodies, until an immunoenzymatic (EIA) methods (ELISA, Western-blotting) in late 60’s was worked out. The immunoenzymatic tests are very useful because of their simplicity and realiability. But there is one more excellent test named “Colorzyme” (presented by Immuno-Concept Corporation from USA) worked out by combining of the EIA and IIF tests. More and more new-founded resources of marker autoantibodies and methods force to introduction into standardization both methods and specimens on which they are marked. During properly executed strategy of ANA assessment usually a multi-stage (“cascade”) methodology is used. In the first stage a screening test (usually IIF-ANA or immunoperoxidase “Colorzyme” method based in Hep-2 cells and ELISA-screen are used). Next (second) step – if ANA are positive we intend to establish of ANA specificity and eventually in the third step so called ANA fine-specificities are assessed of course if there is a clinical demand. Fourth stage is needed only in case, when we were unable to confirm in the tested serum any typical specificity of ANA and it is usually done by combining biochemical and immunochemical methodology. Strict following of these procedures guaranting us in prevalence of the tested sera the possibility (more certainty) that specificities are assessed properly, reproducibility of results, let us to avoiding mistakes and what even more important – generation reasonable costs of diagnostics.